Comparative Study on Biochemical Properties and Antioxidative Activity of Cuttlefish (Sepia officinalis) Protein Hydrolysates Produced by Alcalase and Bacillus licheniformis NH1 Proteases. (20th July 2011) - Balti, Rafik; Bougatef, Ali; El Hadj Ali, Nedra; Ktari, Naourez; Jellouli, Kemel; Nedjar-Arroume, Naima; Dhulster, Pascal; Nasri, Moncef
Abstract : Antioxidative activities and biochemical properties of protein hydrolysates prepared from cuttlefish ( Sepia officinalis ) using Alcalase 2.4 L and Bacillus licheniformis NH1 proteases with different degrees of hydrolysis (DH) were determined. For the biochemical properties, hydrolysis by both enzymes increased protein solubility to above 75% over a wide pH range. The antioxidant activities of cuttlefish protein hydrolysates (CPHs) increase with increasing DH. In addition, all CPHs exhibited antioxidative activity in a concentration-dependent manner. NH1-CPHs generally showed greater antioxidative activity than Alcalase protein hydrolysates (P < 0.05 ) as indicated by the higher 1, 1-diphenyl-1-picryhydrazyl (DPPH) radical scavenging activity and ferrous chelating activity. Both Alcalase and NH1 protein hydrolysates were able to retard lipid peroxidation andβ -carotene-linoleic acid oxidation. Alcalase-CPH (DH = 12.5%) and NH1-CPH (DH = 15%) contained 75.36% and 80.11% protein, respectively, with histidine and arginine as the major amino acids, followed by glutamic acid/glutamine, serine, lysine, and leucine. In addition, CPHs have a high percentage of essential amino acids made up 48.85% and 50.04%. Cuttlefish muscle protein hydrolysates had a high nutritional value and could be used as supplement to poorly balanced dietary proteins.